MANAJEMEN SUMBERDAYA SANTRI (PESERTA DIDIK) DI PONDOK PESANTREN BAITUL ARQOM BALUNG - Huda, Hairul (Universitas Muhammadiyah Jember, 2018)
Santri—i.e., students in Islamic boarding school—resources are one of the elements in the management of Islamic boarding schools. Santri are the first consumer of the service management provided by educational institutions such as Islamic boarding schools. As the main consumer, there is a need for a good and orderly management system for santri so that the objectives of Islamic boarding schools are more directed and can be optimally achieved. Hence, Islamic boarding schools have to carry out resource management for santri so they are able to recruit santri who are truly qualified, are able to adapt, and can put visions and missions of the school into practice. Formulations of this study are as follows: 1. How to design Santri resource planning at Bairul Arqom Islamic Boarding School, Balung? 2. What systems are used for the purpose of recruitment and selection of Santri at Bairul Arqom Islamic Boarding School, Balung? 3. What type of orientation and placement processes of Santri resources are used in Bairul Arqom Islamic Boarding School, Balung?, and 4. How santri resources at Islamic Boarding School Bairul Arqom Islamic Boarding School, Balung, are evaluated? The method used in this study is a qualitative method with data obtained through argumentation. Sources of the data are from interviews, observation and documentation of the data owned by the Islamic boarding school. The results show that activities in santri resource management carried out in Baitul Arqom Islamic boarding school, Balung, are as follows: 1. The design of Santri resource planning is periodically designed and arranged based on the needs and results of discussion among selected committee, 2. Open recruitment patterns involve external sources (e.g., alumni recommendation), and the selection processes involve administrative selection. 3. The orientation is done formally in the form of Khutbatul asry and a week of introduction, 4. Assessment of santri is done in three ways, namely a writing test, speaking test, and daily observation.